In situ depot comprising phase-change materials that can sustainably release a gasotransmitter H2S to treat diabetic wounds. (November 2017) - Lin, Wei-Chih; Huang, Chieh-Cheng; Lin, Shu-Jyuan; Li, Meng-Ju; Chang, Yen; Lin, Yu-Jung; Wan, Wei-Lin; Shih, Po-Chien; Sung, Hsing-Wen
Abstract: Patients with diabetes mellitus are prone to develop refractory wounds. They exhibit reduced synthesis and levels of circulating hydrogen sulfide (H2 S), which is an ephemeral gaseous molecule. Physiologically, H2 S is an endogenous gasotransmitter with multiple biological functions. An emulsion method is utilized to prepare a microparticle system that comprises phase-change materials with a nearly constant temperature of phase transitions to encapsulate sodium hydrosulfide (NaHS), a highly water-labile H2 S donor. An emulsion technique that can minimize the loss of water-labile active compounds during emulsification must be developed. The as-prepared microparticles (NaHS@MPs) provide an in situ depot for the sustained release of exogenous H2 S under physiological conditions. The sustained release of H2 S promotes several cell behaviors, including epidermal/endothelial cell proliferation and migration, as well as angiogenesis, by extending the activation of cellular ERK1/2 and p38, accelerating the healing of full-thickness wounds in diabetic mice. These experimental results reveal the strong potential of NaHS@MPs for the sustained release of H2 S for the treatment of diabetic wounds.